Technical Curriculum Implementation and Evaluation Framework - Narsico, Lalaine O.; Narsico, Peter G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study was a response to unemployment, a pervading social problem. One of the solutions to the problem was the training of a workforce that makes them employable. To implement this solution, efforts from all sectors of society need to align. This study takes off from the vantage point of vocational training centers. Specifically, this was about the formulation and application of a technical curriculum implementation and evaluation framework. It identified curriculum implementation components and their subsequent details from actual curriculum-related practices of a group of vocational training centers. Components were identified through observations, informal interviews, and curriculum-related document reviews. Based on streamlined components, a survey questionnaire was made and was conducted to assess the levels of practice of identified curriculum implementation components in the training centers through the responses of technical directors and instructors. Analysis of Variance (ANOVA) was used to test whether there was a significant difference between the ratings from the two groups of respondents. The following items were the conclusions. Curriculum implementation components were streamlined, formulating an alternative cyclical mechanism for vocational training curriculum implementation and evaluation. Competency transfer and competency assessment were emphasized due to their importance in a vocational training program. There was no significant difference in the responses of the two groups of respondents. Finally, it was found that the training centers can still improve at least a level in all components of curriculum implementation which implies the need for all training personnel to address areas of concern.